THE ROLE OF EDUCATION IN EMPOWERING LIFE THROUGH THE DEVELOPMENT OF THE YOUNG GENERATION OF COMMUNITY 5.0: PERAN PENDIDIKAN DALAM MENDAYAGUNAKAN KEHIDUPAN MELALUI PENGEMBANGAN GENERASI MUDA MASYARAKAT 5.0 - Bukit, Andrio (LPPM UPMI, 2023)
Education is a means that is very important for human survival, this is because education is a sector that can create human intelligence in carrying out their lives, the importance of education so that all necessities of life can easily be obtained. The development of information technology is currently reaching all areas of people's lives, including the field of education. Even education in the era of society 5.0, allows students or students in learning activities side by side with robots that have been designed to replace the role of educators. So what about the education system in Indonesia? This paper examines the role of education in empowering life through developing the younger generation of society 5.0.